(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the current status of knowledge and practice regarding routine hand hygiene among nursing students at the School of Medicine and Pharmacy, Tra Vinh University. Methods: A cross-sectional descriptive study was conducted among 205 nursing students at the School of Medicine and Pharmacy, Tra Vinh University. Data were collected using a structured questionnaire and analyzed using descriptive statistics. Results: The proportions of students with adequate knowledge and correct practice of hand hygiene were 75.1% and 79.5%, respectively. The highest rate of correct knowledge was observed in understanding the six steps of hand hygiene (85.9%). Regarding practice, the highest compliance was recorded for hand hygiene before performing aseptic procedures on patients (88.8%), while the lowest compliance was observed after contact with equipment and items in patient rooms (58.0%). A higher academic year (fourth-year compared with second-year students) was significantly associated with adequate knowledge (OR: 6.12; 95% CI: 2.58 to 14.49) and correct practice (OR: 3.16; 95% CI: 1.32 to 7.54). Conclusion: Nursing students demonstrated generally good knowledge and practice of routine hand hygiene; however, certain practices remain limited, particularly hand hygiene after contact with items and equipment in patient rooms.